Seismic Site Response Simulation of Jakarta subsoils due to 5.4 MW Banten Earthquake July 7th 2020 - Muhammad Fatih Qodri (Retii, 2020)
The potential descruction could be affected by long-distance earthquakes since the vibrations could appear amplification of ground shake during the wave propagation. On July 7th 2020, the 5.4 Mw earthquake happened at Banten Province affiliated with intraslab activities where the Indo-Australian Plate is submerged beneath the Eurasian Plate. The earthquake epicenter is relatively far away from the downtown Jakarta, i.e. about 95 km. However, some people in Jakarta could feel the shaking during the earthquake. It indicates that the long-period shaking could happen during the earthquake. Futhermore, this study aims to interpret the amplification effect in Jakarta. The next generation attenuation (NGA) model is implemented to generate the ground motion for the investigated sites. Simulation of non linear one-dimensional seismic site response is then performed to observe the soil behavior and ground motion parameters on the investigated sites. In general, the results could describe the amplification effect on Jakarta subsoils. The results are also addressed to make the awareness of the earthquakes for people of Jakarta and Indonesia in general.